2000
DOI: 10.1021/jf990521+
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Sulfoxides and Alliinase Activity of Some Allium Species

Abstract: The flavor precursors of 17 species belonging to the Alliaceae family were analyzed by HPLC, and results were evaluated with respect to the classification of species into their genus, subgenus, and section. Identification and quantification of these precursors were carried out by synthetic and natural reference materials. In addition, nine of these species were investigated in terms of their alliinase activity. Alliinase (EC 4.4.1.4) catalyzes the conversion of odorless (+)-S-alk(en)yl-L-cysteine sulfoxides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 21 publications
5
103
2
Order By: Relevance
“…SAC is one of the major organosulfur compounds found in aged garlic extracts, and the allyl moiety appears to be crucial for any biologic activity. Similarly, SPC has been identified in extracts prepared from Allium species such as garlic and onion (10,19). Several studies have indicated that SAC and SPC can inhibit TG and cholesterol biosynthesis in cultured rat hepatocytes (8,11).…”
Section: Discussionmentioning
confidence: 98%
“…SAC is one of the major organosulfur compounds found in aged garlic extracts, and the allyl moiety appears to be crucial for any biologic activity. Similarly, SPC has been identified in extracts prepared from Allium species such as garlic and onion (10,19). Several studies have indicated that SAC and SPC can inhibit TG and cholesterol biosynthesis in cultured rat hepatocytes (8,11).…”
Section: Discussionmentioning
confidence: 98%
“…The plant is used to prepare a variety of local and special foods. Cysteine sulfoxides and alliinase activity of A. paradoxum have been reported recently [9]. To the best of our knowledge there is no scientific reported about antioxidant and antihemolytic activities of this species.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the main objective of was to explore the possibility of using combined microwave-convective drying technique for processing of garlic and assessment of the quality of finished product. Many studies have recently provided strong evidence that most of these biological functions of garlic are attributed to allicin [37,38]; Tulasidas TN [39] reported that no compound outside the thiosulphate, of which allicin is about 60-80% has been found that accounts for a significant portion of the pharmaceutical activities of crushed garlic at levels representing normal human consumption (2-5 g/d).…”
Section: Methods Of Drying Hot Air Dryingmentioning
confidence: 99%